Learning-within-Relationship as Context and Process in Adult Education: Impact on Transformative Learning and Social Change Agency - Carole Barlas (Adult Education Research Conference, 2001)
This paper presents one major finding from a broader set of findings encompassed in a doctoral dissertation. The study describes the learning experiences of twenty adults who identified themselves as significantly transformed by their participation in a doctoral program in transformative learning. This result describes and explores the impact of learning within the context of relationship on how adults changed their basic assumptions about themselves and the way they act in their social worlds.